POLARIZATION FUNCTIONS OF NATURAL GYROTROPIC MEDIA EXISTING IN EXTERNAL MAGNETIC FIELD - Gevorgyan, A. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2001)
The propagation of electromagnetic waves through a layer of naturally gyrotropic media in an external magnetic field is considered. The problem is solved by a method 4× 4 matrix of Beremann. The Jones matrixes are constructed; the reflection and transmission coefficients, the polarization azimuth and ellipticity of a passing wave are calculated. The specific features of polarization functions of own modes, eigen polarizations and polarization functions of an incident wave at which one of the own modes is not exited are investigated. It is shown, that in these media under certain conditions three own modes are excited.´